Sistem Pendukung Keputusan Penerima Bantuan Rumah Layak Huni Menggunakan ROC Dan SAW - Heni Kriswanti; Syarifah Putri Agustini Alkadri; Izhan Fakhruzi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In addition to food, clothing, and shelter, shelter is one of the basic human needs. The house is also a living space and serves as protection from climate change and other living things. This research introduces the Ranc Order Centroid (ROC) method and the Simple Additive Weighting (SAW) method in the decision support system of home aid recipients, and develops a decision support system that can be used by aid providers. The system uses PHP and MySql programming languages as databases. The methodology used is Unified Modeling Language (UML) as the system design. The test used is black box testing. The end result of this research is the creation of a series of decision support systems for recipients of home assistance and communities in need of support.